Contestation and Actualization of Ijma’ in the Formation of Law in Indonesia - Madnur; Musyaffa Amin Ash Shabah; Sofyan Munawar; Imam Addaruqutni (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
The contestation of ijma' issues among conventional and contemporary scholars has generated pros and cons among academics and legal practitioners in establishing legal provisions to address existing problems. This understanding has influenced the perspectives of relevant parties in comprehending the doctrine of ijma'. On one side, it is stated that ijma' cannot be realized after the era of the companions, while on the other side, it is argued that ijma' can be learned through more progressive thinking. This paper is normative legal research with a statutory regulatory approach contextualized in Islamic law, especially the provisions combined with the results of scholars' ijtihad. The findings of this research indicate that ijma' has significance in the development of law in Indonesia. However, legislating ijma' into national law in Indonesia has its dynamics, influenced by political, social, religious, and cultural factors and other elements that can trigger polemics amidst the diversity of Indonesian society. Keywords: Ijma', scholars' contestation, and legal legislation